2021
DOI: 10.1016/j.tranon.2020.100971
|View full text |Cite
|
Sign up to set email alerts
|

GD2-specific chimeric antigen receptor-modified T cells targeting retinoblastoma – assessing tumor and T cell interaction

Abstract: Highlights This is the first report on targeted T cell therapy against retinoblastoma (RB). A novel GD2-specific CAR T with safety switch effectively killed RB. Repetitive antigen exposure, the tumor cells gradually lost GD2 expression and increased PD-L1 expression. The first report on RB tumor evolvement after targeted T cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
(26 reference statements)
0
11
0
Order By: Relevance
“… 43 Research and development of NB tumor therapy has focused on GD2, including GD2 antibodies and GD2 CAR-T cells. 44 Many of these studies have exhibited powerful anticancer abilities in animal models. Among them, the anti-GD2 monoclonal antibody dinutuximab (ch14.18) has been approved by the US Food and Drug Administration, and dinutuximab β (ch14.18/CHO) has been approved by the European Medicines Agency for high-risk neuroblastoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Research and development of NB tumor therapy has focused on GD2, including GD2 antibodies and GD2 CAR-T cells. 44 Many of these studies have exhibited powerful anticancer abilities in animal models. Among them, the anti-GD2 monoclonal antibody dinutuximab (ch14.18) has been approved by the US Food and Drug Administration, and dinutuximab β (ch14.18/CHO) has been approved by the European Medicines Agency for high-risk neuroblastoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, others developed local immunotherapy formulations also based on anti-GD2 CART cells, including an injectable hydrogel to prolong their localization at the site of injection. After IVi administration, the formulation resulted in complete tumor response and no recurrence or ocular toxicity in orthotopic xenograft models (137,138) (Figure 2).…”
Section: Gangliosides and Other Targets For Immunotherapymentioning
confidence: 97%
“…Earlier clinical studies have shown CAR T-cell therapy to be effective against RB. U pon co- culturing with GD2-antigen and GD2-CAR T cells, nearly 80% of RB cells died in 24 h, and approximately 100% cell mortality was achieved in 3 days ( 24 ).…”
Section: Retinoblastomamentioning
confidence: 99%